Paysages viticoles : paysages ruraux ? - Soazig Darnay (Projets de Paysage)
Wine-growing landscapes establish a link between nature and culture, they have increasingly been the object of heritagisation in Europe in answer to a societal demand and a need for recognition on the part of the profession. At the same time the wine-growing business has been impacted by globalisation and illustrates the complexity of the relation between the local and global dimensions. Wine tourism, also globalised, is increasingly used as a communication and marketing tool at company as well as national levels. The wine-growing landscape has therefore become a tool and at the same time an outcome of this phenomenon.